PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK CARIBBEAN BREEZE DI SUPERMARKET HYPERMART - Ikbal Aulianto Ajipranata (Majalah Ilmiah Widyacakra, 2019)
The title of the research is the Effect of Brand Image, Price, and Product Quality on Purchasing Decisions at Hypermart Supermarket. Purchasing decisions are influenced by several factors including product attributes such as brand image, price, and product quality and purchasing decisions is the process by which a person actually decides to buy a product. The purpose of this study was to determine the effect of brand image, price, and product quality on purchasing decisions at the Hypermart Supermarket. Samples from this study were as many as 100 Caribbean Breeze user customers. Data were analyzed using a computer program SPSS version 22. The data analysis method used was multiple linear analysis methods. The data used are primary data and secondary data obtained through questionnaires obtained through questionnaires that measure using a Likert Scale. The results obtained from statistical analysis showed that the magnitude of the influence of brand image, price, product quality on purchasing decisions at Hypermart Supermarket is by testing f test hypotheses and t test with the results that product quality variables (X3) partially have a positive and significant influence individually to customer satisfaction with t-test results of 3.0260 <t-tab 1.664 and sig 0.002 on purchasing decisions (Y) and simultaneously the variable brand image, price, and product quality have a positive and significant effect on Caribbean Breeze product purchasing decisions in Badung with the results of F-count of 3.565 and sig 0.017. the results of the test of determination that simultaneously brand image, price and product quality have an influence of 10.1% on purchasing decisions of Carribbean Breeze products in Hypermart Supermarket while the remaining 90.9% is influenced by other variables not discussed in this study.